PATHOGENETIC ASPECTS OF STATINS’ APPLICABILITY IN COMBINATION TREATMENT OF PATIENTS WITH UTERINE FIBROIDS AND EXTRAGENITAL PATHOLOGIES - Zhurakivskyi, V.M. (World of Medicine and Biology, 2017)
The article involves materials of thesis research conducted in accordance with the plan of SHEE «Ivano-Frankivsk national medical university» and is a part of academic research work of the department of obstetrics and gynecology named after I.D. Lanovyi “Clinical and medico-social grounding of effective methods for the prediction of pathologic states, diagnosis and treatment of women during pregnancy and other periods of their life” (state registration number 0104U008431).